(untitled) (Historia, 2021)
The Natal Archives of the Republic of South Africa, which formspart of the state archival services of the country and is under the controlof the Director of Archives in Pretoria, contains a large number ofinteresting and valuable government records but also houses severalimportant collections of private papers which are the property of thearchives and which, under certain conditions, are available to researchers.In the category of private collections are the papers which areknown to students as the Henry Francis Fynn Papers.Henry Francis Fynn was one of the earliest British pioneers in whatwas later to become the province of Natal in the llepublic of South Africa.He was born in 1803 in the United Kingdom and was educated at Christ’sHospital, London, England. At the age of thirteen he found his wayto Cape Town and there joined his father who, it was claimed, hadvisited the port of Natal as early as 1806 on a voyage from Australia tothe Cape. In 1818 Henry Francis Fynn journeyed to Delagoa Bay, inPortuguese East Africa, as supercargo on a commercial speculation. Itwas on this trip that Fynn first came into contact with the Zulu tribeswhich then inhabited a large portion of Africa South of the Zambesi River,and it was then that Fynn first appreciated the possibilities of trade withthe interior regions of Southern Mrica.Back in Cape Town, he joined forces with a certain LieutenantFarewell and together they persuaded the Governor of the Cape Colonyto grant them permission to trade with Natal.It was Fynn, however, who reached Natal first and it was he whodetermined to make the first contact with the great Zulu king, Chaka,who had earned the reputation of being the Attila of Southern Africa. Itis very possible that Fynn was the first white man to be seen by Chaka.A small British settlement, mainly concerned with trade with theZulus of the interior, was soon established at the Bay, near the presentthriving port of Durban. This settlement was continually menaced bythe might of Chaka, but Fynn was able to ingratiate himself with theZulu chief by restoring Chaka to health after his arm had been piercedby an enemy spear. This ministration saved the British at the portfrom Chaka’s ire and gained for Fynn a grant of land almost 6,000 squaremiles in extent